1993
DOI: 10.1159/000261582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sucrose Concentration on the Cariogenic Potential of Pooled Plaque Fluid from Caries-Free and Caries-Positive Individuals

Abstract: Pooled plaque samples were obtained from (1) coronal surfaces of two groups of caries-free (CF) subjects (2) coronal ‘white-spot’ surface areas of a group of caries-positive (CP) subjects, and (3) exposed, sound root surfaces of root caries-free (RCF) and root caries-positive (RCP) subjects. The plaque samples were obtained before and 3 min after a 1 min rinse with a 0.5,1, 2, 5 and 10% sucrose solution. Plaque fluid was then isolated from each plaque sample by centrifugation and analyzed for inorganic ions, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
7
15
1
Order By: Relevance
“…All the no-rinse plaque fluid values shown in table 3 are consistent with values previously obtained in this and in other laboratories [Carey et al, 1986;Margolis et al, 1993;Margolis and Moreno, 1994;Vogel et al, 1997Vogel et al, , 1998Vogel et al, , 2000a. The no-rinse whole-plaque total fluoride values are, however, higher than previously obtained [Vogel et al, 1992[Vogel et al, , 1997.…”
Section: Discussionsupporting
confidence: 91%
“…All the no-rinse plaque fluid values shown in table 3 are consistent with values previously obtained in this and in other laboratories [Carey et al, 1986;Margolis et al, 1993;Margolis and Moreno, 1994;Vogel et al, 1997Vogel et al, , 1998Vogel et al, , 2000a. The no-rinse whole-plaque total fluoride values are, however, higher than previously obtained [Vogel et al, 1992[Vogel et al, , 1997.…”
Section: Discussionsupporting
confidence: 91%
“…The 'no-rinse' and postfluoride rinse (time 0) plaque pH, phosphate, free calcium (table 3) are similar to previous values [Carey et al, 1986;Moreno, 1992, 1994;Margolis et al, 1993;Vogel et al, 1992Vogel et al, , 1997Vogel et al, , 1998Vogel et al, , 2001. The values were also similar to those obtained in the in vitro acidification and water rinse studies described in Materials and Methods [Vogel et al, , 2001, in which an NaF rinse was also examined, so that the results obtained here can be compared with these previous results.…”
Section: Discussionsupporting
confidence: 87%
“…The pH and organic acid concentrations after sucrose rinsing (table 3) are also similar to the reported values using similar methods [Margolis and Moreno 1992;Margolis et al, 1993]. In studies using different methodologies, these concentrations were somewhat greater [Pearce et al, 1999;Oliveby et al, 1990] or less [Higham and Edgar, 1989] than reported here but, in all cases (tables 3, 4), a large increase in lactate and a decrease in the concentration of other organic acid anions, particularly acetate, were observed after sucrose administration.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As indicated at the outset, oral food clearance is very complex, depending on physiological, physical, and microbiological parameters [6,14,15]. Therefore, such a simple rating system does not describe the true metabolic processes taking place in the oral cavity during the time sugar clears the mouth.…”
Section: Resultsmentioning
confidence: 99%